Communication Styles used by Effective EFL Teachers in Classroom Interaction - Suharni Sudirman; Haryanto Atmowardoyo; Kisman Salija (ELT Worldwide: Journal of English Language Teaching, 2018)
This research was conducted to find out; (1) the characteristics of the effective teachers based on the students’ perception; (2) to describe the communication styles used by EFL teachers in classroom interaction; (3) to find out when and why the teacher used the aggressive, assertive and passive style. This research applied mixed method research. The instruments of this research were questionnaire, observation, and interview. The sample of this research consisted of 265 students at SMA Ummul Mukminin boarding school Makassar, in academic 2017/2018. The subjects of the research were three experienced English teachers. The research finding based on students’ perception to the EFL English teachers in each class showed that Mrs. Wal got 73.5% categorized as very effective teacher, Ms. WN got 76.9% categorized as very effective teacher, Mr. As got 65.2% categorized as  effective teacher. The teacher was very effective described by students who had 20 positive attitudes that have to be done and 24 negative attitudes for ineffective teachers that must be avoided. Furthermore, the research revealed three findings in communication styles used by teachers. The first was aggressive style, the second was assertive style, and the third was passive style. The teachers used those styles based on the context and situation during English classroom process. The most dominant communication style used by the teacher was aggressive.